2017
DOI: 10.1108/ijhma-01-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Small firm performance: an empirical analysis in Malaysian housing construction industry

Abstract: Purpose The purpose of this paper is to evaluate the importance of innovation for the performance of small firms in the construction sector. Furthermore, this paper also examines the influence of several factors related to entrepreneurial capital (entrepreneurial value, business strategy, experience and training) on small firm performance in the sector. Design/methodology/approach This study uses primary data of 255 small firms in the construction sector under the category of small contractors (G1). Stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Research results related to the effect of service quality on performance do not always give the same results as the literature. Previous research results (Mahmood, Zahari, Yaacob, & Zin, 2017) did not show any effect of automated service quality dimensions on financial performance.…”
Section: Introductionmentioning
confidence: 56%
“…Research results related to the effect of service quality on performance do not always give the same results as the literature. Previous research results (Mahmood, Zahari, Yaacob, & Zin, 2017) did not show any effect of automated service quality dimensions on financial performance.…”
Section: Introductionmentioning
confidence: 56%
“…In El-Hallaq and Tayeh (2015), companies apply most of the strategies. Mahmood et al (2017), andOyewobi, Windapo andRotimi (2017) have concluded that there is evidence that corporate values and strategy are important internal factors in determining a company's performance, in addition to other organizational factors.…”
Section: Discussionmentioning
confidence: 99%
“…It implies that the company's attributes are different from rivals and creates consumer loyalty (PORTER, 1986, p. 49). Mahmood et al (2017), analyzing 255 small construction companies in Malaysia using questionnaires and descriptive analysis and multiple regression have concluded that there is evidence that business values and strategy are important internal factors in determining a company's performance, in addition to others organizational factors. Oyewobi, Windapo and Rotimi (2017) reach the same conclusion by evaluating 72 large companies in South Africa using structural equations of partial least squares.…”
Section: Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…, Lisboa et al (2016),Danso et al (2016),Bahari et al (2017),Ozaralli and Rivenburgh (2016),Mahmood et al (2017), Meroño-Cerdán et al (2018 andIsaga (2018). On the other hand, other personality traits such as need for achievement (Hypothesis 1) and propensity of risk taking (Hypothesis 3) were not shown to have a positive link with performance of SEPs by results (H1: b = -0.014, t = 0.179; H3: b = 0.060, t = 0.870).…”
mentioning
confidence: 85%